Aplikasi Persamaan Diferensial Dalam Mengestimasi Jumlah Penduduk dengan Menggunakan Model Eksponensial dan Logistik - Nasrun Rozikin; Ketut Sarjana; Arjudin Arjudin; Nurul Hikmah (Griya Journal of Mathematics Education and Application, 2021)
This research was aimed to describe the application of differential equations of the population growth model in the City of Mataram, which is an exponential and logistic models for estimating the population of the City of Mataram in 2024. The research method used in this research is descriptive research with a qualitative approach carried out by observation and analyze the subject. The subject of this research was data on the population of the City of Mataram from 2006 to 2019. Meanwhile, to determine the accuracy and validity of the research data, the triangulation of sources was used. The data used comes from the Dispendukcapil and BPS the City of Mataram. The research result, it shows that the exponential model has an accuracy rate of 99,6%, which is very accurate, while for estimating with a logistic model each criterion is very accurate but the confidence level is 97,9%. Estimation results also show that population growth in the city of Mataram in the future will slowdown in its growth every 2 years, with an average decrease of 0.5%.